2006
DOI: 10.1002/pi.2060
|View full text |Cite
|
Sign up to set email alerts
|

Chitosan and N‐carboxymethylchitosan: I. The role of N‐carboxymethylation of chitosan in the thermal stability and dynamic mechanical properties of its films

Abstract: Chitosan (degree of deacetylation of 90.2%) and N‐carboxymethylchitosan (N‐CMCh) (degree of substitution of 18.5%) were analyzed using thermogravimetric analysis in order to determine their thermal stability. Also, their films were evaluated using scanning electron microscopy (SEM) and mechanical and dynamic mechanical analysis (DMA). Both polymers showed a thermal degradation peak at Tm ∼ 250 °C, with Tonset and weight loss of 175 °C and 62% and 190 °C and 35% for chitosan and N‐CMCh, respectively. N‐CMCh sho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
30
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 69 publications
(36 citation statements)
references
References 23 publications
2
30
0
1
Order By: Relevance
“…Decomposition of cross-linked low molecular weight chitosan pyruvic acid derivative is expected to happen after 564.1 • C as shown in the TG/DSC studies. The product had high decomposition temperature because it was thermally stable, and high temperature was required for decomposition (Anirudhan & Rijith, 2009;Cestari, Vieira, Matos, & dos Anjos, 2005;Miranda et al, 2006;Mourya, Inamdar, & Tiwari, 2010). Fig.…”
Section: Scanning Electron Microscope (Sem)mentioning
confidence: 98%
“…Decomposition of cross-linked low molecular weight chitosan pyruvic acid derivative is expected to happen after 564.1 • C as shown in the TG/DSC studies. The product had high decomposition temperature because it was thermally stable, and high temperature was required for decomposition (Anirudhan & Rijith, 2009;Cestari, Vieira, Matos, & dos Anjos, 2005;Miranda et al, 2006;Mourya, Inamdar, & Tiwari, 2010). Fig.…”
Section: Scanning Electron Microscope (Sem)mentioning
confidence: 98%
“…16 To improve the solubility of Ch in water at neutral pH, which limits application, chemical modification with N-carboxymethylation has been studied. 17,18 a different line, Felício et al 19 reported that the inner hydrophobic domains of biocompatible N-carboxymethylchitosan (N-CMCh) nanoparticles may be useful for hydrophobic drug incorporation.…”
mentioning
confidence: 98%
“…Carboxylate chitosan derivatives could be characterized using analytical techniques such as Fourier transform infrared spectroscopy (FTIR) (Boamah et al, 2014;Chen and Park, 2003;De Britto et al, 2011), 1 H NMR spectroscopy (Hjerde et al, 1997;Muzzarelli et al, 1994), 13 C NMR spectroscopy (Chen and Park, 2003;Rinaudo et al, 1992), differential scanning calorimetry (DSC) (Kittur et al, 2002;Miranda et al, 2006), titrimetry (Ge and Luo, 2005), viscometry (Mourya et al, 2010), gel permeation chromatography (Miranda et al, 2006), capillary zone electrophoresis (Fu et al, 2007), among others. Recently, potentiometric titration method has been developed to simultaneously determine DD, DS and distribution factor of -COONa or -COOH in carboxymethyl chitosan (Kong, 2012).…”
Section: Characterization Of Carboxylate Chitosan Derivativesmentioning
confidence: 99%